2018
DOI: 10.13005/msri/150305
|View full text |Cite
|
Sign up to set email alerts
|

Designing Fructose Stabilized Silver Nanoparticles for Mercury(II) Detection and Potential Antibacterial Agents

Abstract: The synthesis of fructose stabilize silver nanoparticles (AgNPs) was attempted in the proposed work. It was found that developed AgNPs played an important role as colorimetric nanoprobes for the estimation of metal ions. The prepared AgNPs were characterized by UV-Vis, IR, XRD, SEM techniques. XRD-pattern of AgNPs, concluded that particles are well dispersed and present in a fcc system and average size was found to be 16.6 nm. AgNPs displayed specific and sensitive recognition to Hg2+ by colorimetric analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The observed peaks are 401, 406, 407, 408, and 409 nm of the silver nanoparticles with honey plus 20, 40, 60 80, and 100 mL of silver nitrate solution respectively. These peaks coincide with the reported peaks of the AgNPs in other literature [2][3][9][10]16]. It was observed that the broad and highest peak comes from the Honey + 60mL AgNO3 solution at wavelength 407 nm.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The observed peaks are 401, 406, 407, 408, and 409 nm of the silver nanoparticles with honey plus 20, 40, 60 80, and 100 mL of silver nitrate solution respectively. These peaks coincide with the reported peaks of the AgNPs in other literature [2][3][9][10]16]. It was observed that the broad and highest peak comes from the Honey + 60mL AgNO3 solution at wavelength 407 nm.…”
Section: Resultssupporting
confidence: 89%
“…The lowest peak is at the 409 nm of the Honey plus 100mL AgNO3 solution. Moreover, increasing the amount of silver nitrate solution shifted from shorter to longer wavelengths as shown in the inset graph [16]. Redshifting occurs due to the increase in particle size of the synthesized AgNPs at an increasing amount of silver nitrate solution.…”
Section: Resultsmentioning
confidence: 84%
“…The degree of coverage around the particles increases with polymer molecular weight, thus inhibiting further Ag + reduction on the surface to a higher degree, resulting in smaller particles compared to systems utilizing smaller MW stabilizers, where the particles have a larger free surface, rendering particle growth possible. The sample prepared with 40k PVP demonstrated prominent Debye-Scherrer rings, corresponding to 2.35 and 1.44 Å lattice distances, or Miller indices of (111) and (220), respectively; to a smaller degree, rings corresponding to (220) and (311) were detected, verifying the chemical composition of the particles [8,18,21,22]. AgNPs synthesized by 50k PVP also demonstrated these rings, although in a much more diffuse manner, due to their smaller particle size.…”
Section: Nanoparticle Morphology and Crystallinitymentioning
confidence: 69%
“…For example, Ag 55 Cu 45 NPs show a single (111) peak, which corresponds to a lattice parameter falling in between the lattice parameter for Ag (0.409 nm) and that for Cu (0.363 nm). 20,21 For NPs with Ag % > 75%, the observation of a separate small (111) shoulder peak (2θ = 37) may be attributed to the presence of a small degree of phase segregation for a different composition.…”
Section: ■ Results and Discussionmentioning
confidence: 99%